An artificial self-assembling peptide with carboxylesterase activity and substrate specificity restricted to short-chain acid p-nitrophenyl esters - Liu, Yanfei; Gan, Lili; Feng, Peili; Huang, Lei; Chen, Luoying; Li, Shuhua; Chen, Hui (Frontiers in Chemistry, 2022)
Natural enzymes possess remarkable catalytic activity and high substrate specificity. Many efforts have been dedicated to construct artificial enzymes with high catalytic activity. However, how to mimic the exquisite substrate specificity of a natural enzyme remains challenging because of the complexity of the enzyme structure. Here, we report artificial carboxylesterases (EC 3.1.1.1) that are specific for short chain fatty acids and were constructed via peptide self-assembly. These artificial systems have esterase-like activity rather than lipase-like (EC 3.1.1.3) activity towards p-nitrophenyl esters. The designer peptides self-assembled into nanofibers with strong β-sheet character. The extending histidine units and the hydrophobic edge of the fibrillar structure collectively form the active center of the artificial esterase. These artificial esterases show substrate specificity for short-chain acids esters. Moreover, 1-isopropoxy-4-nitrobenzene could function as a competitive inhibitor of hydrolysis of pNPA for an artificial esterase